Frequency, risk factors and symptomatology of iatrogenic withdrawal from opioids and benzodiazepines in critically Ill neonates, children and adults: A systematic review of clinical studies. (19th December 2018) - Duceppe, Marc‐Alexandre; Perreault, Marc M.; Frenette, Anne Julie; Burry, Lisa D.; Rico, Philippe; Lavoie, Annie; Gélinas, Céline; Mehta, Sangeeta; Dagenais, Maryse; Williamson, David R.
Summary: What is known and objective: Many critically ill patients are exposed to opioids and benzodiazepines at high doses for prolonged periods, and upon discontinuation of these drugs, they may be at risk for iatrogenic withdrawal. Although this syndrome was associated with worse outcomes in the critically ill, limited guidance exists regarding its evaluation, prevention and treatment. This systematic review examined the frequency, risk factors and symptomatology of iatrogenic withdrawal from opioids and/or benzodiazepines in critically ill neonates, children and adults. Methods: The literature search was conducted in PubMed, Medline, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane register of systematic reviews, DARE, CINAHL, Trip database, CMA infobase and NICE evidence from inception to February 2018. Grey literature was examined. We included studies reporting frequency, risk factors or symptomatology of iatrogenic withdrawal of opioids, benzodiazepines (or both) in critically ill patients. We considered all study designs except case reports and case series. We excluded studies on neonatal abstinence syndrome, alcohol withdrawal, studies on chronic opioid and/or benzodiazepine users and studies on prevention or treatment of withdrawal in critical care patients. Two independent reviewers applied the inclusion and exclusion criteria. Pairs of reviewers independently abstracted data and evaluated methodological quality using the Cochrane Collaboration Tool, Newcastle‐Ottawa or QUADAS‐2. Details regarding study design, outcomes, definition, evaluation and type of withdrawal (opioid, benzodiazepine or mixed) were collected. Cumulative doses and duration of opioids and benzodiazepines were collected. Results and discussion: We identified 21 866 unique citations and 153 full texts were assessed for eligibility. Thirty‐four studies were included; the majority were observational and few included adults. In prospective studies, mixed withdrawal was observed in 7.5%‐100% of patients in paediatric studies and ranged from 16.7% to 55% in adults. Symptomatology of withdrawal was not well described. Risk factors included higher cumulative dose and prolonged administration of opioids and benzodiazepines. What is new and conclusion: Iatrogenic withdrawal appears to be a frequent syndrome in critical care patients who received regular doses of opioids and/or benzodiazepines for ≥72 hours. Larger studies are required, especially in critically ill adults, to better define the syndrome and its symptomatology. Abstract : Iatrogenic withdrawal appears to be a frequent syndrome in critical care patients who received regular doses of opioids and/or benzodiazepines for ≥72 hours. Larger studies are required, especially in critically ill adults, to better define the syndrome and its symptomatology.